After the Spirit : a constructive pneumatology from resources outside the modern West - Rogers, Eugene F (Grand Rapids, Mich. : William B. Eerdmans Pub., 2005)
After the Spirit is a learned, eloquent, gracious response to the dearth of theological reflection on the Holy Spirit in the modern Christian West. If you have been wondering where the Spirit went, or what it might mean for the Spirit to befriend the body, or how Barth, Coakley, and Rahner might be brought into fruitful conversation with Bulgakov, Florensky, and Simeon the Elder, then read this book. / by Jeffrey Stout
For those who have found themselves bored by the wilted spinach of recent writing on the Spirit, Rogers offers a real steak. . . . Drawing on a wide range of Greek, Latin, and Syriac patristic sources, as well as engaging a fascinating variety of modern authors, Rogers shapes his theology through close readings of Scripture and tradition. In a way that we have come to expect from Rogers, tradition riffs on Scripture, and Scripture is then allowed to take up the chords of tradition and play something new that draws us back to listen again to the old. Protestant, Catholic, and Orthodox should all find something here to delight and challenge. / by Lewis Ayres
Is there nothing the Spirit can do that the Son can't do better? : or, how the Spirit puzzles a Trinitarian revival -- Is the Spirit superfluous? : or, how the Spirit does economics -- Where the Spirit rests : matter and narrative; or, how the Spirit does material culture -- Resurrection -- Annunciation -- Baptism -- Transfiguration -- Ascension and Pentecost -- About-face -- Epilogue : the Spirit rests on the Son in those who do not know how to pray
Includes bibliographical references (p. 223-243) and indexes
Keywords: Holy Spirit -- Procession